2020
DOI: 10.1371/journal.pone.0226194
|View full text |Cite
|
Sign up to set email alerts
|

Content shared on social media for national cancer survivors day 2018

Abstract: Background Studies estimate that the number of cancer survivors will double by 2050 due to improvements in diagnostic accuracy and treatment efficacy. Despite the growing population of cancer survivors, there is a paucity of research regarding how these individuals experience the transition from active treatment to long-term surveillance. While research has explored this transition from more organized venues, such as support groups for cancer survivors, this paper explores the discourses surrounding cancer sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Furthermore, in a study assessing content posted by cancer survivors on Twitter ® and Instagram ® , Cherian et al found that a more personal and narrative approach dominated Instagram. In contrast, Twitter ® posts concentrated on more factual aspects [ 9 ]. Therefore, we decided to study Instagram ® , which is the fifth-most popular social medium after Facebook ® , Youtube and two communicators (WhatsApp ® and Messenger ® ) [ 10 ] and offers more user-friendly content.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study assessing content posted by cancer survivors on Twitter ® and Instagram ® , Cherian et al found that a more personal and narrative approach dominated Instagram. In contrast, Twitter ® posts concentrated on more factual aspects [ 9 ]. Therefore, we decided to study Instagram ® , which is the fifth-most popular social medium after Facebook ® , Youtube and two communicators (WhatsApp ® and Messenger ® ) [ 10 ] and offers more user-friendly content.…”
Section: Discussionmentioning
confidence: 99%
“…25 Cherian et al evaluated 193 posts across both platforms on national cancer survivors day, finding that images were used in 87 (74%) and 33 (44%) posts on Instagram and Twitter, respectively. 26 Instagram has frequently been used by patients following orthopaedic surgery to share personal stories with a positive, uplifting tone. 5,20,21,26 This visual platform has also been used to enhance medical education.…”
Section: Discussionmentioning
confidence: 99%
“…26 Instagram has frequently been used by patients following orthopaedic surgery to share personal stories with a positive, uplifting tone. 5,20,21,26 This visual platform has also been used to enhance medical education. In 2019 Douglas et al performed an audit-based inquiry by searching terms associated with anatomy, medicine, and education on Instagram.…”
Section: Discussionmentioning
confidence: 99%
“…YouTube has been used by patients with cancer to share personal stories [ 35 ]. Moreover, a recent study explored cancer survivorship on social media and found that the content shared by survivors displayed their physical, emotional, and psychological health [ 36 ]. Although Instagram was used mainly for sharing images posted by survivors themselves or others, Twitter was used primarily for sharing facts and fundraising.…”
Section: Discussionmentioning
confidence: 99%